JUSTNORTH Justice Database ... - Wood-Donnelly, Corine; Ohlsson, Johanna; Przybylinski, Stephen; Sidortsov, Roman; McCauley, Darren; Skillington, Tracey; Mitchell, Don (Zenodo, 2022)
JUSTNORTH is an EU-funded climate action project exploring the perspectives and values that stakeholders can bring to Arctic economic decision-making. The JUSTNORTH Justice Database is the final outcome of the project's work with theories and frameworks of justice. It is a database of bibliographic materials organised in folders related to schools of justice philosophy (i.e., libertarianism, feminism) and applied approaches (i.e., environmental, energy) in justice. It also includes folders for grey literature and justice organisations. The database is intended to be a study and research resource for its users, both within JUSTNORTH and for those researching issues of justice beyond the project. This dataset includes Access and Excel versions that can be downloaded, there is also a living version on Zotero (https://www.zotero.org/groups/4662062/justnorth_justice_database/library). JUSTNORTH received funding from the European Union’s Horizon 2020 research and innovation programme under grant agreement No ...